2019
DOI: 10.5101/nbe.v11i2.p200-214
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Antimicrobial Activity of Imipenem in Combination with Silver Nanoparticles towards S. fonticola and Pantoea sp.

Abstract: Silver nanoparticles have been considered as powerful antimicrobial agents recently, especially with the increasing incidence of diseases associated with biofilm and multi-drug resistant pathogens. The aim of this study was to synthesize silver nanoparticles by biological and chemical methods and combination with imipenem to eradicate biofilm-forming bacteria at phenotypic and genotypic levels. The biosynthesis of silver nanoparticles was done by using Enterobacter cloacae (cell-free suspension) while chemosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Their antimicrobial properties [42][43][44] are widely used in medicine sector such as antibacterial sprays, medicine, wound dressings [45], respirators, and heart valves [46][47][48][49][50]. Ag-NPs have also exhibited antimalarial [51], antiviral [52], anticancer [53][54][55], anti-plasmodial [51], larvicidal [56], antifungal [57,54,42,58,59], biofilm forming bacteria [60,61], and pupicidal activity [62], disinfections, water and air purification, agriculture [63,64], etc. These properties of silver encourage its use in, cosmetics, clothing and numerous household products, contraconceptives, detergent, dietary supplements, cutting boards, socks, shoes, cell phones, laptop keyboards, and children's toys [65,66].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their antimicrobial properties [42][43][44] are widely used in medicine sector such as antibacterial sprays, medicine, wound dressings [45], respirators, and heart valves [46][47][48][49][50]. Ag-NPs have also exhibited antimalarial [51], antiviral [52], anticancer [53][54][55], anti-plasmodial [51], larvicidal [56], antifungal [57,54,42,58,59], biofilm forming bacteria [60,61], and pupicidal activity [62], disinfections, water and air purification, agriculture [63,64], etc. These properties of silver encourage its use in, cosmetics, clothing and numerous household products, contraconceptives, detergent, dietary supplements, cutting boards, socks, shoes, cell phones, laptop keyboards, and children's toys [65,66].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Green synthesis utilizing Citrullus lanatus fruit rind as a reductant and capping agent yields stable, spherical Ag-NPs with an average diameter of 17.96 ± 0.16 nm [110]. Ag-NCs reduced using NaBH4 showed the formation of cubical NCs with size range from 22-28 nm and 56-72 nm for biological synthesis [60]. Moosa et al also reported an increase in the size of silver kaolinite nanocomposites (Ag/Kln NCs) with the increase in silver nitrate concentration.…”
Section: Effected Of Ag Ions Concentration To the Controlling Size Of Ag-npsmentioning
confidence: 99%
“…The biofilm-forming bacteria displayed antibiotics resistant patterns. Many studies approved that biofilm bacteria were multi-drug resistance bacteria (18,19,21,22). The reasons behind their resistance were antibiotics penetration difficulty(23), extracellular matrix act at shield and chelating agent (24) and low bacterial metabolic state (25).…”
Section: Figure 2 Congo Red Agar Indicating the Biofilm Formation Bacteriamentioning
confidence: 99%
“…But there is no study about date palm AgNPs antibacterial effect on biofilm-forming bacteria. Many studies about anti-biofilm activity of AgNPs synthesis by other methods showed a high response to be antibiofilm (30)(31)(32) . Antibacterial activity of green synthesis AgNPs in the present study may be related to attach to the surface of the cell membrane disturbing permeability and respiration functions of the cell (33).…”
Section: Antimicrobial Effects Of Agnps On Biofilm Forming Bacteriamentioning
confidence: 99%
“…Silver has long standing antibacterial compound, and silver nanoparticles are more potent in antimicrobial effect than normal scale [7,8]. Silver nanoparticles increase bacterial susceptibility to antibiotics when combined with them as synergistic effect especially in biofilm infection [9], for example, nitrofurazone increased its effect in silver present [10].…”
Section: Introductionmentioning
confidence: 99%